Analisis Pengelolaan Wakaf Produktif Dimasjid Azizi Kecamatan Jelutung Kota Jambi - Youdhi Prayogo; Jevi Saputra; Sapaat Ramadan (STIKes Ibnu Sina Ajibarang, 2024)
This thesis is entitled Analysis of Productive Waqf in Azizi Mosque, Jelutung District, Jambi City and aims to find out the analysis of productive waqf, the utilization of productive waqf results and the view of Islamic economics on the analysis of productive waqf in Azizi Mosque, Jelutung District, Jambi City. In this study using a qualitative approach that is useful for providing information on facts and data on the mechanism of analysis of productive waqf Dimasjid Azizi Jelutung District Jambi City, with data collection methods by conducting observations, interviews and documentation. From the results of this study it was found that: (1) Analysis of productive waqf at Dimasjid Azizi from the management aspects of Planning, Organizing, Leading and Controlling, has not gone well. Because of the various problems that occur. (2) The utilization of waqf results carried out is mostly used for consumptive use, especially for religious activities such as recitation, and others. There has been no utilization to improve the economy, in the health sector or other social sectors. (3) the view of the Islamic economy on productive waqf which in its implementation is carried out with a rental system, where the rental of productive waqf assets at the Azizi Mosque is not found to have an element of usury for the delay in payment, even if there is a delay in payment the nazhir gives time and opportunity to pay it.